A Review: Automated Testing of Object Oriented Modules Using ML Unit Tool - Er. Krishan Kumar; Vasu Dev (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The field of testing has been the subject of a great number of inquiries; nevertheless, the conventional research methods suffer from the drawbacks of having a limited scope and being inflexible It is important to test both manually and automatically, thus it is necessary to look at object-oriented modules both ways. Therefore, in the case of both procedural and object-oriented systems, it is necessary to investigate both manual and automated testing methods. More up-front engineering is desperately needed in the modern embedded software development process. The car industry has performed almost little preliminary testing. The advent of executable modeling tools like ML Unit makes pre-production testing more practical The research will include looking at previous work that has been done in the field of automated testing and considering the role that Matlab plays in both automated and manual testing. During the testing phase, we are focused on the procedural and object-centric modules, and we are looking at the problems that are connected with the traditional testing system, such as its inability to scale and its lack of flexibility. In addition, we are examining the challenges that are caused by the conventional testing system.